Daya Dukung Kawasan dan Daya Dukung Rill pada Ekowisata Sungai Mudal Banyunganti, Jatimulyo, Kulon Progo, DIY - Maulidya Anggun Ayumadany; Johan Danu Prasetya; Muammar Gomareuzzaman (Dinamika Lingkungan Indonesia, 2022)
Mudal River ecotourism is located in the Menoreh Hills which is a geological protected area and the area around the springs in the RTRW of Kulon Progo Regency. Since 2015 the Mudal River has been used as a tourist spot in the ecotourism category. These ecotourism activities have increased significantly from year to year when viewed from secondary visitor data for 2015-2018. The study was conducted to determine the value of the carrying capacity of the area and the real carrying capacity which is an effort to prevent damage that occurs in ecotourism areas in protected areas. The method used in this research is a survey and field method. Data on the parameters of carrying capacity and area and real carrying capacity were obtained from the survey and field activities. Based on the results and data processing carried out, it was found that the carrying capacity of the area (DDK) was 701 people/day (consisting of DDK utilization of playing water 637 people/day, DDK utilization of sitting relaxed 57 people/day, and DDK utilization of camping 7 people/day). Meanwhile, the real carrying capacity value is 1151 people/day. The two results obtained are still far above the existing visitors to the Mudal River Ecotourism so the carrying capacity of ecotourism activities is still in accordance with the value of the carrying capacity of the area and the real carrying capacity.